Análisis del nivel de rentabilidad en las ventas de la Empresa Becromal S.A. durante el periodo 2018 y 2019 - Espinoza Cox, Maria Mercedes (2020)
This case study seeks to know the level of profitability in sales that the Becromal S. A Company had during 2018 and 2019 through the use of financial analyzes carried out on the accounting information that the entity has in order to know a little more about the fluctuations that have existed in both periods. Becromal is an entity that is dedicated to the cultivation of rice and soybeans, that is why it is important that a profitability analysis is carried out throughout the company to determine if it is efficient and in case of detecting shortcomings, take certain strategies to increase the level of yourself and get a higher profit. Profitability is the ability of an entity to generate economic benefits and if its percentage is good, the owner can continue to invest in it. Financial analysis allows to interpret and analyze the financial statements of companies through the application of horizontal and vertical analysis. The horizontal analysis allows to know the absolute and relative variations existing between one period to another and to know if there has been a decrease or increase The vertical analysis compares the balance sheet accounts or the income statement with each other, but expressed in percentages, and thus establish the efficiency of the company with respect to the periods that are analyzed. The financial ratios are an important tool since they allow to measure the relationship of two economic figures obtained from the statements of the company to be evaluated in the case of Becromal, only the profitability ratios were used